Amoxicillin Haptenation of α-Enolase is Modulated by Active Site Occupancy and Acetylation - González-Morena, Juan M.; Sánchez-Gómez, Francisco J.; Vida, Yolanda; Pérez-Inestrosa, Ezequiel; Salas, María; Montañez, María I.; Altomare, Alessandra; Aldini, Giancarlo; Pajares, María A.; Pérez-Sala, Dolores (Frontiers in Pharmacology, 2022)
Allergic reactions to antibiotics are a major concern in the clinic. Beta-lactam antibiotics are the class most frequently reported to cause hypersensitivity reactions. One of the mechanisms involved in this outcome is the modification of proteins by covalent binding of the drug (haptenation). Hence, interest in identifying the corresponding serum and cellular protein targets arises. Importantly, haptenation susceptibility and extent can be modulated by the context, including factors affecting protein conformation or the occurrence of other posttranslational modifications. We previously identified the glycolytic enzyme alpha-enolase as a target for haptenation by amoxicillin, both in cells and in the extracellular milieu. Here, we performed an in vitro study to analyze amoxicillin haptenation of alpha-enolase using gel-based and activity assays. Moreover, the possible interplay or interference between amoxicillin haptenation and acetylation of alpha-enolase was studied in 1D- and 2D-gels that showed decreased haptenation and displacement of the haptenation signal to lower pI spots after chemical acetylation of the protein, respectively. In addition, the peptide containing lysine 239 was identified by mass spectrometry as the amoxicillin target sequence on alpha-enolase, thus suggesting a selective haptenation under our conditions. The putative amoxicillin binding site and the surrounding interactions were investigated using the alpha-enolase crystal structure and molecular docking. Altogether, the results obtained provide the basis for the design of novel diagnostic tools or approaches in the study of amoxicillin-induced allergic reactions.